THE STUDY OF LEGENDS IN ENGLISH FOLKLORE GENRES - Tosheva Dilbar Muzaffar kizi (American Journals, 2022)
Learning English is impossible without taking into account the history of England, the elements of its culture and creativity, including the peculiarities of English folklore. But it is a huge number of myths and legends, ballads, poems, reflecting the development and formation of the country, the formation of the mentality of the people.